SWOT ANALYSIS TO FORMULATE DEVELOPMENT STRATEGY FOR BINA LAKSANA VILLAGE ENTERPRISE - Mulyani, Sri; Yuliafitri, Indri; Armania, Gia Prima (LPPM Univ. Ibn Khaldun Bogor, 2024)
This research analyzes the internal and external factors that influence the development of BUMDes Bina Laksana in Sukalaksana Village, Garut, using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. This analysis aims to develop appropriate strategies to support the sustainability of the BUMDes' business in empowering the village economy and reducing urbanization. Strengths of BUMDes include tourism potential and village superior products, while weaknesses include limited capital, market access, and HR skills. Opportunities include government support and tourism potential, but the BUMDes faces threats such as competition with other villages and climate change impacts. Strategy recommendations include optimization of superior products, digital marketing, HR development, and business diversification to strengthen BUMDes' position as a local economic driver.